Bundling Information Goods: The Case of E-Journals - TAN, Yong (Institutional Knowledge at Singapore Management University, 2007)
With the development of the Internet, e-business has become popular. Increasingly, e-journals are being sold via the Internet. E- journals have two main characteristics: one is the low marginal cost associated with access; the other is the large number of items. For the commercially motivated seller, the issue of bundling a large number of low marginal cost items so as to maximize profits needs to be dealt with. In this thesis, a solution by way of an intermediate bundle is proposed. It is found that the profit obtained under the proposed procedure is 4% to 5% higher than that under the Chuang-Sirbu procedure, which is currently adopted by many sellers. Furthermore, when the number of products involved is not extremely large, the proposed procedure yields a profit level that is closer to the first price discrimination profit level than the Armstrong two-part tariff procedure. In this thesis, a heuristic rule to facilitate the determination of the optimal intermediate bundle size is also proposed. This is designed to avoid the lengthy simulation procedure that will be needed otherwise.